A study on zakat distribution in Bank Rakyat / Nurin Atika Mohamad Sapari - Mohamad Sapari, Nurin Atika (Academy of Contemporary Islamic Studies (ACIS), 2016)
Situations today illustrates that people prefer to give zakat directly to asnaf without going through the center of zakat. This will impact a reduction in the number of zakat collection by the institution of zakat every year. Nowadays, financial institutions can distribute zakat fund through the cooperation with zakat institutions. This study attempts to examine the unit of zakat distribution in Bank Rakyat and to analyse the function of Bank Rakyat in the disbursement of zakat to asnaf. Furthermore, this research will show the number of decreases in the amount of distribution of zakat fund in every state in Malaysia from 2013 until 2015 at Bank Rakyat.The results show that a combination of zakat institutions and Bank Rakyat in managing the distribution of zakat will benefit both parties.